Some Properties of Chaotic Modified of Bogdanov Map (JOURNAL OF ADVANCES IN MATHEMATICS, 2021)
In this  research to the modified dynamics of Bogdanov's map  studied, and the  found sensitivity to the initial conditions of the modified map  found as well as the Lyapunov exponent .the general characteristics of the map  by the diffeomorpism. Finally we boosted my research  with matlab to find chaotic areas